MANFORSERV (Mangrove Forest Conservation) Application Design with WebGIS Technology - Sitanggang, Andri Sahata; Hasti, Novrini; Syafariani, R Fenny (Universitas Komputer Indonesia, 2024)
The total area of ​​mangrove forests in Indonesia is 25% of the total world-famous mangrove forests along 100,000 kilometers of coastline. Handling that can be done is to rebuild and restore the mangrove forest itself. The existence of GIS (Geographical Information System) provides a solution to overcome this problem. The GIS concept used includes spatial analysis in determining the location for planting coral reef forest seedlings in accordance with environmental characteristics. The GIS concept is implemented through an online mangrove seed donation system. The purpose of this research is to design an online donation system based on GIS. The method applied was the descriptive method and action (action). In designing the system, the methods used were object-oriented approach and prototype development methods. With this research, a system will be produced in the form of an online donation application in carrying out mangrove forest conservation, making it easier for people to conserve mangrove forests in Indonesia.